Primary umbilical endometriosis coexisiting with multiple uterine fibroids: A case report. (May 2022) - Mba, S.G.; Omeke, C.A.; Enebe, J.T.; Anyanwu, O.C.
Abstract: Introduction: Uterine fibroids and endometriosis are independent causes of infertility/subfertility in women of reproductive age. Primary umbilical endometriosis is rare. Presentation of case: Here, we report a case of primary umbilical endometriosis coexisting with multiple uterine fibroids in a 35 year old nulliparous woman who presented with abdominal swelling as well as cyclical pain and swelling of the umbilicus without any previous surgery. She had abdominal myomectomy and excision of the umbilical lesion with histological confirmation of uterine fibroids and umbilical and peri-umbilical endometriosis. Discussion: Primary umbilical endometriosis should be considered as a possible differential diagnosis in cases of umbilical disorders even if the patient has no typical symptoms of pelvic endometriosis. The clinical features include an umbilical swelling (90%), often associated with cyclical pain (81.5%) and bleeding or discharge (49.2%); while some patients may be asymptomatic. The diagnosis of umbilical endometriosis could be made based on clinical findings but histological confirmation is the gold standard for diagnosis. The definitive treatment for umbilical endometriosis is surgical excision. Conclusion: Although rare, primary umbilical endometriosis may coexist with uterine fibroids and should be suspected in women of reproductive age who complain of cyclical umbilical disorders in addition to abdominal swelling or other symptoms of uterine fibroids. Highlights: Primary umbilical endometriosis is rare. Although rare, a high index of suspicion should be maintained for umbilical endometriosis. The definitive treatment for umbilical endometriosis is surgical excision. The diagnosis is confirmed by histopathological examination.